2011
DOI: 10.1111/j.1467-9396.2011.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

International R&D Networks

Abstract: This paper considers the Goyal and Moraga‐Gonzalez (2001) model of strategic R&D collaboration networks in the open economy framework. The R&D is the d'Aspremont and Jacquemin (1988) process innovation and collaboration takes the form of research joint ventures (RJV) in which firms cooperate in R&D but compete in product markets. Countries decide whether to establish free‐trade links while firms decide whether and with whom to form RJVs. A double‐layer pairwise stability concept is introduced to characterize e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
0
19
5
Order By: Relevance
“…In the theoretical R&D literature, the most common stable R&D structure is a complete network (Goyal and Moraga-Gonzalez 2001; Goyal and Joshi 2003; Song and Vannetelbosch 2007; Deroian 2008; Westbrock 2010; Zu et al. 2011; Konig et al. 2012; Zirulia 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the theoretical R&D literature, the most common stable R&D structure is a complete network (Goyal and Moraga-Gonzalez 2001; Goyal and Joshi 2003; Song and Vannetelbosch 2007; Deroian 2008; Westbrock 2010; Zu et al. 2011; Konig et al. 2012; Zirulia 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2011). Song and Vannetelbosch (2007) studied the case when there are three firms belonging to different countries and producing homogeneous goods.…”
Section: Introductionmentioning
confidence: 99%
“…However, having in mind that research collaborations and networks are nowadays considered as essential elements to generate innovations in the knowledge based economy in general [17]–[19], and also in the pharmaceutical sector, the analysis of such cross-country R&D collaborations constitutes an important additional element when investigating the dominance of the US in global pharmaceutical innovation. This is related to the increasing complexity of finding new drugs, on the one hand, and, on the other hand, to the dramatically improving accessibility and mobility of research resources across geographical space [20].…”
Section: Introductionmentioning
confidence: 99%
“…What is important in these ventures is a pairwise stable R&D, where both firms have the same strength in this activity. This way, opportunistic behaviour can be diminished (Zu et al, 2011). Zhang et al (2010) added that inter-firm cooperation and competition coexist in strategic alliances and both factors increase knowledge acquisition, although from different motivational bases.…”
Section: Best Practices For International Randd Partnershipsmentioning
confidence: 99%
“…When firms adopt an equity joint venture structure, the opportunistic behaviour can be mitigated due to the shared ownership (Oxley and Sampson, 2004). Zu et al (2011) suggested another type of partnership by a research joint venture (RJV). In this partnership, the firms cooperate in R&D but compete in product markets.…”
Section: Best Practices For International Randd Partnershipsmentioning
confidence: 99%